Information Structure Affects the Resolution of the Subject Pronouns Er and Der in Spoken German Discourse - Miriam Ellert (Discours)
Two visual-world eye-tracking experiments were designed to investigate the resolution of ambiguous German pronouns, the personal pronoun (er) and the d-pronoun (der) in spoken discourse. Specifically, the influence of the order of mention and the information status of the antecedent candidates on the resolution preferences following canonical and non-canonical antecedent structures was explored. The results suggest that the two pronominal forms have different coreference functions when they follow canonical topic-comment antecedent structures, in that personal pronouns prefer first-mentioned topical antecedents and d-pronouns second-mentioned non-topical antecedents. However, after non-canonically marked topic-focus antecedent structures, the pronouns had overlapping functions, namely an overall preference towards the second-mentioned focused entity. The findings suggest that pronoun resolution is affected by the information status of the antecedent candidates and that resolution preferences change across antecedent word orders.